ANALISIS TURUNNYA DAYA TARIK VISUAL DALAM IKLAN OLX PADA TELEVISI - Bagas Pangestu (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2019)
Advertising is one of the promotion media that is used to sell a product or service, usually advertisements in the form of images, messages, sounds, and also videos that use multimedia facilities in the form of television. One application is an online shop called OLX that uses television advertising as a promotional tool. But advertising in this time, often ignored by the audience, especially on television advertising that not everyone can see the ad because the time being broadcast is not effective and those who watch television have diminished and also the interest of the ad itself. This makes the appeal of advertisements decline especially on television advertisements and conducted research by interviewing 5 respondents to find out the response to the attraction of television advertising today. The results of the analysis of the interview prove that the advertisements that are launched do not necessarily produce the appropriate response.